A phase I, single‐sequence, open‐label study to evaluate the drug–drug interaction between hetrombopag and cyclosporine in healthy Chinese subjects - Li, Fengshan; Lin, Hongda; Feng, Shiyin; Cai, Linrui; Zhang, Lingli; Feng, Sheng; Liu, Xiaohong; Chen, Zhuo; Zou, Qin; Wu, Yiwen; Su, Xu; Shen, Kai; et al. (British journal of clinical pharmacology, 2023)
Aims This study aims to evaluate the drug–drug interaction (DDI) between hetrombopag and cyclosporine in healthy Chinese subjects. Methods Twenty‐six eligible subjects enrolled in this single‐centre, single‐sequence, open‐label, DDI study with 3 treatment periods, receiving 5 mg hetrombopag once on Day 1, 100 mg cyclosporine twice daily from Day 11 to Day 15 and 5 mg hetrombopag + 100 mg cyclosporine on Day 16. Serial blood samples were collected for pharmacokinetic evaluation. Adverse events were monitored throughout the study. Results The plasma hetrombopag geometric mean ratios (90% confidence interval) of maximum plasma concentration, area under the plasma concentration–time curve (AUC) from predose to time of last quantifiable sample and AUC to infinity of coadministration of hetrombopag with cyclosporine vs. hetrombopag alone were 95.97% (70.08–131.43%), 105.75% (75.04–149.04%) and 104.19% (74.71–145.32%), respectively, indicating multiple doses of cyclosporine had minimal effects on hetrombopag exposure. The geometric mean ratios (90% confidence interval) of maximum blood concentration and AUC at steady state during a dosing interval for blood cyclosporine of coadministration vs. cyclosporine alone were 100.49% (91.89–109.89%) and 100.81% (107.88–103.82%), respectively, suggesting a single dose of hetrombopag had no impact on the exposure of cyclosporine. Coadministration of hetrombopag with cyclosporine was generally well tolerated. Conclusion No clinically significant DDI was observed when coadministration of hetrombopag with cyclosporine. The results of this study will inform the appropriate use of this combination therapy both in clinical trials and clinical settings.